Noise generation during surgical osteotomies in Oral and Maxillofacial Surgery – is it harmful?. (26th May 2019) - Tocaciu, S.; Liu, A.; Rutherford, N.
Abstract: Aim: Oral and maxillofacial surgeons typically spend over 20 h in the operating theatre every week. Many of their procedures involve the use of powered bone and tooth cutting devices, which generate potentially harmful levels of noise. Prolonged exposure to loud noises is associated with hearing loss, increased serum cortisol levels, detrimental cardiovascular outcomes, and poor task performance. This study explores the noise generation of common powered tooth and bone cutting devices in a theatre setting. Materials and methods: Both compressed air and electric devices were tested. For compressed air devices three burs were tested – jet, round and fissure. Results: The study found that at the proximity of the patient and surgeon, all tested devices generated noise above the safe threshold of 75 decibels. At the distance of 1 m or more (corresponding to the anaesthetist and scout nursing staff), the Surgairtome and oscillating saw were the only powered osteotomy devices below the safe noise level. Conclusions: This study explores the impact of noise generation from powered osteotomy devices. This may have health implications for theatre staff, the surgeon, anaesthetist, and the patient.